Electropolishing of Cylindrical Copper Cavities - Ahmed, A.M.; Darewish, Mona (Asian Journal of Chemistry, 2012)
The rates of electropolishing of cylindrical copper cavities were studied by measuring the limiting current for anodic dissolution of copper from phosphoric acid using a cylindrical anode placed inside cavity. Variables used were cavity diameter, cavity length, phosphoric acid concentrations and temperatures. It's found that the rate of electropolishing decreases by increasing cavity, phosphoric acid concentrations increases by diameter of cavity, depth and temperatures. Thermodynamic parameters were given. The data can be correlated by the equation Sh = 1.54 (Sc.Cr)0.29(d/h).